Seroprevalence of Helicobacter pylori/CagA Antibodies in Guatemalan Gastric Cancer Patients: Association of Seropositivity with Increased Plasma Levels of Pepsinogens but not Soluble Urokinase Plasminogen Activator Receptor - Fernández Botrán, Rafael (2020)
Infection by Helicobacter pylori is a major risk factor for gastric cancer (GC), the second leading cause of cancer-related death worldwide. Although biomarkers such as pepsinogens (PGs) and soluble urokinase plasminogen activator receptor (suPAR) may have diagnostic and/or prognostic value in patients with GC, their levels may be affected by H. pylori infection. The aim of this study was to investigate the association of the presence of antibodies to H. pylori and cytotoxin-associated gene A (CagA) with plasma levels of PGs and suPAR in a cohort of Guatemalan GC patients and controls. To this end, levels of suPAR, Pepsinogens I and II (PGI and PGII), and antibodies to H. pylori and CagA toxin were determined by ELISA in plasma samples from 67 GC patients and 136 matched healthy controls. Seropositivity for CagA was significantly higher in patients with GC than in controls. Pepsinogens II and suPAR levels were higher and PGI/PGII ratios were lower in GC patients than in controls. There was a significant association of H. pylori seropositivity status with increased levels of PGII and lower PGI/PGII ratios, particularly in the control (non-GC) population. The levels of suPAR were not significantly affected by H. pylori or CagA seropositivity status. These results suggest that the seropositivity status for H. pylori and CagA need to be taken into account during the GC diagnostic process.